A study of impulsivity as a predictor of problematic internet use in university students with disabilities - Pino, María J.; Herruzo, Carlos; Lucena, Valentina; Trenados, Yolanda; Herruzo, Javier (Frontiers in Psychiatry, 2024)
Introduction The role played by impulsivity in problematic internet use (PIU) is the object of much debate among researchers. Some studies emphasize its importance, while others suggest mental distress or personality traits may be more crucial. More research into the issue is clearly needed—especially in at-risk populations like people with disabilities. The objectives of this study were therefore to investigate the relationship between PIU and impulsivity among university students with disabilities, and to develop a specific predictive model for this group that would include psychological and life-functioning variables. Methods A cross-sectional design was used with a sample of 240 Spanish university students with disabilities from seven universities. Several instruments were used for data collection: a sociodemographic questionnaire, the Internet Addiction Test (IAT), the Clinical Outcomes in Routine Evaluation-Outcome Measure (CORE-OM), and NEO-FFI-R. Results The results indicated that impulsivity is significantly correlated with PIU, as indeed it also is with other factors like conscientiousness and social functioning problems. The study's regression model explained nearly 50% of PIU variance, with impulsivity, personality traits, wellness and health indicators, and social media usage as predictive variables. Discussion This suggests that interventions should consider these psychological and lifestyle variables as a means of mitigating PIU risks in students with disabilities. The findings identify a need for further longitudinal studies to understand the causality and develop targeted prevention strategies.